Numerical algorithms for differential-algebraic equations of multibody dynamics - Sun, Wei (2016 16th International Conference on Control, Automation and Systems (ICCAS), 2016)
For solving stiff differential-algebraic equations, we present the discrete dynamic iteration processes for multibody dynamics problems. The waveform relaxation iteration based on the Runge-Kutta(RK) methods is studied. The convergence results is obtained. This method provides an effective iterative process to the numerical approach for multibody systems.